Fitoremediasi Posfat Menggunakan Tanaman Eceng Gondok Pada Limbah Cair Domestik - Yanti, Febri; Simanjuntak, Hendra (PendIPA Journal of Science Education, 2024)
High levels of phosphate in waters, the majority of which comes from domestic liquid waste containing detergents. To overcome pollution arising from domestic liquid wastewater, wastewater treatment is absolutely necessary. The urgency of this research is very important in that an environmental mitigation engineering system is sought, so that it can reduce or even eliminate these pollutants if possible. The waste processing technique using plants is known as phytoremediation. Phytoremediation using water hyacinth plants. The analytical method in this study used a completely randomized design (RAL) where each treatment was repeated three times with an additive linear model for a two-factor factorial design with an environmental design in the form of RAL which was analyzed using the SPSS program. If the results of the analysis of variance show an F-count value > Ftable 0.5, a further test is carried out using the Tukey further test (honest significant difference). The results of this research were that the pH value was 6.9, close to the normal pH of water, and the temperature was around 26-25 0C. The BOD level decreased further over 7 days. Phosphate levels also experienced changes in concentration levels which decreased on day 7. The TSS value increased greatly. The TSS value greatly increased the yield and the color changed to cloudy brown.